The order Axinellida (Porifera: Demospongiae) in California - Turner, Thomas L; Pankey, M Sabrina (Zootaxa, 2023)
Sponges are common and diverse in California, but they have received little study in the region, and the identities of many common species remain unclear. Here we combine fresh collections and museum vouchers to revise the order Axinellida for California. Seven new species are described: Endectyon (Endectyon) hispitumulus, Eurypon curvoclavus, Aulospongus viridans, Aulospongus lajollaensis, Halicnemia litorea, Halicnemia montereyensis, and Halicnemia weltoni. One new combination is also described, and two existing species are reduced to junior synonyms, resulting in a total of 13 species; a dichotomous key to differentiate them is provided. DNA data from 9 of the 13 species is combined with publicly available data to produce updated global phylogenies for the order.